A review study on theoretical comparison between time-dependent analysis models for prestressed concrete bridges - Naser, Ali Fadhil (Penerbit Universiti Kebangsaan Malaysia, 2022)
Particularly, concrete material involvements creep under a continuous load and practices shrinkage due to variations in humidity proportion. These physical properties variations growth over time. Prestressed losses according to concrete creep and shrinkage will lead to loss of compression strength for concrete. Time-dependent analysis is important and essential for two types of prestressed concrete which are pretensioned and posttensioned with the effect of time, variations in the structural pattern, and high erection loads influence the structural performance and protection of structure for the duration of erection and when complete. Creep and shrinkage are the main time-dependent parameters of concrete. They are important parameters in the design of prestressed concrete structures such as bridges. The objective of this study is to review the analysis models of time-dependent parameters for prestressed concrete bridges by using shrinkage and creep factors equations to determine the strain of time-dependent parameters. Creep and shrinkage parameters were selected to review the effect of these parameters on the properties of prestressed concrete. Nine analysis methods for creep and shrinkage of concrete were reviewed in this study. These models include ACI-209 model, PCI-BDM model, CEB-FIP-90 model, AASHTO-LRDF model, Shams and Kahan model, NCHRP-496 model, B3 model, GL2000 model, and AFREM model. It was recommended that using this methodology to determine shrinkage and creep factors for prestresssed concrete bridge and comparing between the results of analysis models.